Implementation of The Economic Order Quantity Method For Inventory of Goods - Muhammad Iqbal Kusrachmansyah; Erni Seniwati; Acihmah Sidauruk (IJISTECH (International Journal of Information System and Technology), 2022)
The inventory system that is being carried out at this time is by manual method where the inventory is still made using Microsoft Office in the form of Microsoft Word and Microsoft Excel in which data is written about data on the presentation of basic food items sold, expenditure of goods and orders. However, the presentation of goods is less efficient and effective. By looking at this situation and condition, the author makes a system "implementation of the economic order quantity method for inventory" where this system can help shop owners and employees who work at the shop make their work easier and also help streamline and be effective in recording the goods sold , issuing goods, and also ordering goods. In this system the author uses the PHP programming language with a MySQL database, where later the data will be entered and stored in the database and connected to PHP programming so that inventory control is easier, more efficient, and effective.